The Effect of Laser Wavelength on Porous Silicon Formation Mechanisms - Abdulzahra, Narges Zamil (Nahrain University College of Engineering Journal, 2011)
In this work, the effects of coherent radiation (Laser) with different wavelength and photon energy during the electrochemical etching process on the structural characteristics PS samples were investigated. The porosity values were measured by depending on the microstructure analyses and gravimetric measurements. Surface morphology, layer thickness, pore diameter, pore shape, wall thickness and etching rate were studied by depending on Scanning electron-microscopic (SEM) images.